Literasi Perbankan Syariah Untuk Meningkatkan Akselerasi Inklusi Keuangan (Studi pada Bank Syariah Indonesia (BSI) KCP Probolinggo) - Syaiful Suib, Mohammad; Amelia, Lina (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
This research aims to analyze the literacy used by syariah banking in increasing the acceleration of financial inclusion at BSI KCP Probolinggo. This research explores the impact of the role of syariah banking literacy on accelerating financial inclusion, in the context of inclusive and sustainable syariah banking. This topic was chosen to fill the gap in understanding the contribution of syariah banking literacy to the development of financial inclusion, which is a crucial aspect in building a sustainable syariah financial institutional environment. The qualitative approach used in this research is a case study type. The selection of objects at BSI KCP Probolinggo was based on considerations because the bank is one of the syariah financial institutions that plays an important role in the development of syariah finance in the Probolinggo area. The techniques used to collect research data consist of in-depth interviews, participant observation, and documentation. Where the research data consists of primary data obtained from several research informants, namely the director of BSI KCP Probolinggo, three employees of BSI KCP Probolinggo, five customers of BSI KCP Probolinggo. Meanwhile, secondary data was obtained from national and international journals that were relevant to research. The data analysis techniques used consist of data reduction, data display, and drawing conclusions. The research results show that syariah banking literacy in increasing financial inclusion is carried out by providing financial education, holding promotions and marketing, and conducting outreach through various media. Syariah banking literacy has a significant impact on increasing financial inclusion.